Arenópolis sequence, evolution of a marginal basin in the Neoproterozoic Goiás magmatic arc, central Brazil. (March 2021) - Carneiro, Jônatas; Fuck, Reinhardt; Dantas, Elton Luiz
Abstract: The Goiás Magmatic Arc in central South America and the Arabian-Nubian shield record major phases of Tonian subduction during a period marked otherwise by dominant tectonic quiescence. Several basins were formed in convergent tectonic settings and their rock record may enlighten some aspects of the tectonic history of the Rodinia Supercontinent, such as provenance patterns and pathways and subsidence mechanisms. In this study, we present the results of geologic mapping and geochronologic analyses of detrital zircon grains of the Tonian volcanic-sedimentary Córrego do Santo Antônio unit, Arenópolis Sequence, of the Goiás Magmatic Arc, Brasília Belt, central Brazil. It is formed of several mafic-ultramafic rocks exposed along eastwards dipping thrust sheets. These bodies are covered by thin layers of metachert and marble. Between the thrust faults, voluminous mica schist and quartzite packages are exposed. Two samples of siliciclastic metasedimentary rocks from an eastern thrust sheet show multimodal age spectra for detrital zircon grains, with a major peak with ages between 1.9 and 2.1 Ga, and minor peaks of 0.99 Ga, 1.2 Ga, ca. 1.4 Ga, 2.45 Ga, 2.75 Ga and ca. 3.0 Ga. One sample of quartzite from the westernmost thrust sheet presents a similar pattern, but with major peaks of 1.2 Ga, 1.55 Ga, 1.85 Ga, and 2.1 Ga and minor peaks of 0.9 Ga and 2.55 Ga. Another sample of metagraywacke from the westernmost thrust sheet displays a unimodal pattern, with a peak of 893 Ma and a minor contribution of Mesoproterozoic zircon grains. Geologic field data suggest that the Córrego do Santo Antônio unit represents a Tonian trench basin, which might have received low rates of sedimentation. Aeromagnetic data confirm that these rocks occur along the limit of blocks, corroborating formation in a trench basin. Geochronologic data from one sample corroborate this interpretation. However, the U–Pb isotopic data of the other samples indicate that the sedimentation history is quite more complex. We suggest three possibly complementary hypotheses to explain both geologic and geochronologic data: 1) Metasedimentary rocks were formed in distinct tectonic environments and later were tectonically imbricated; 2) Older metasedimentary rocks were the preferred source for the basin; 3) The basin preferentially received sediments from older terrains by longitudinal turbidity currents. We conclude that the basin, which originated the Córrego do Santo Antônio unit had a link with cratonic areas and received sediments from longitudinal currents. Highlights: New and refined geological mapping of the Tonian Arenópolis Sequence, associated with the Goiás Magmatic Arc. Interpretation of new magnetic data for the area. Detrital zircon geochronology for a marginal basin associated to the Tonian Goiás Magmatic Arc.